Identification of novel candidate genes for Ascochyta blight resistance in chickpea - Françoise Dalprá Dariva; Amlan Arman; Mario Morales; Harry Navasca; Ramita Shah; Sikiru Adeniyi Atanda; Lisa Piche; Hannah Worral; Garrett Raymon; Kevin McPhee; Clarice Coyne; Paulo Flores; et al. (Scientific Reports)
Abstract Ascochyta blight, caused by the necrotrophic fungus Ascochyta rabiei, is a major threat to chickpea production worldwide. Resistance genes with broad-spectrum protection against virulent A. rabiei strains are required to secure chickpea yield in the US Northern Great Plains. Here, we performed a genome-wide association (GWA) study to discover novel sources of genetic variation for Ascochyta blight resistance using a worldwide germplasm collection of 219 chickpea lines. Ascochyta blight resistance was evaluated at 3, 9, 11, 13, and 14 days post-inoculation. Multiple GWA models revealed eight quantitative trait nucleotides (QTNs) across timepoints mapped to chromosomes 1, 3, 4, 6, and 7. Of these eight QTNs, only CM001767.1_28299946 on Chr 4 had previously been reported. QTN CM001766.1_36967269 on Chr 3 explained up to 33% of the variation in disease severity and was mapped to an exonic region of the pentatricopeptide repeat-containing protein At4g02750-like gene (LOC101506608). This QTN was confirmed across all models and timepoints. A total of 153 candidate genes, including genes with roles in pathogen recognition and signaling, cell wall biosynthesis, oxidative burst, and regulation of DNA transcription, were observed surrounding QTN-targeted regions. Further gene expression analysis on the QTNs identified in this study will provide insights into defense-related genes that can be further incorporated into breeding of new chickpea cultivars to minimize fungicide applications required for successful chickpea production in the US Northern Great Plains.